Nuclear delivery of plasmid DNA determines the efficiency of gene expression. (18th May 2019) - Liu, Hui; Yang, Zhen; Xun, Zhe; Gao, Zihao; Sun, Yanping; Yu, Jiankun; Yang, Tianzhi; Zhao, Xiaoyun; Cai, Cuifang; Ding, Pingtian
Abstract: As a cationic non‐viral gene delivery vector, poly(agmatine/ N, N ′‐cystamine‐bis‐acrylamide) (AGM‐CBA) showed significantly higher plasmid DNA (pDNA) transfection ability than polyethylenimine (PEI) in NIH/3T3 cells. The transfection expression of AGM‐CBA/pDNA polyplexes was found to have a non‐linear relationship with AGM‐CBA/pDNA weight ratios. To further investigate the mechanism involved in the transfection process of poly(AGM‐CBA), we used pGL3‐control luciferase reporter gene (pLUC) as a reporter pDNA in this study. The distribution of pLUC in NIH/3T3 cells and nuclei after AGM‐CBA/pLUC and PEI/pLUC transfection were determined by quantitative polymerase chain reaction (qPCR) analysis. The intracellular trafficking of the polyplexes was evaluated by cellular uptake and nuclei delivery of pLUC, and the intracellular availability was evaluated by the ratio of transfection expression to the numbers of pLUC delivered in nuclei. It was found that pLUC intracellular trafficking did not have any correlation with the transfection expression, while an excellent correlation was found between the nuclei pLUC availability and transfection expression. These results suggested that the intracellular availability of pLUC in nuclei was the rate‐limiting step for pLUC transfection expression. Further optimization of the non‐viral gene delivery system can be focused on the improvement of gene intracellular availability.